Perspektif Kajian Budaya: Pelestarian Budaya Melalui Cerpen Anak "Topeng Barong Kakek" Karya Veronica Widyastuti - Atikah Nuha Hibatullah; U’um Qomariyah (Journal of Humanities, Social Sciences, and Education, 2026)
This study aims to examine the representation of cultural preservation in Veronica Widyastuti's children's short story "Topeng Barong Kakek" (Barong Grandpa Mask) from a cultural studies perspective. The focus of this research is how children's literary texts represent local cultural values ​​and function as a medium for transmitting traditions to child readers. The method used was descriptive qualitative, with data collection through reading and note-taking of the short story. Data analysis was conducted by interpreting the cultural elements contained in the story. The results show that the short story represents Balinese culture through the symbolism of the Barong mask as a cultural identity, the figure of the grandfather as the inheritor of tradition, and family relationships as a space for transmitting cultural values ​​between generations. This representation demonstrates that children's literature functions not only as a medium for entertainment but also as an educational tool for introducing and preserving local culture. Thus, the short story "Topeng Barong Kakek" plays a crucial role in building children's cultural awareness through simple and contextual storytelling, making it relevant for use as a medium for cultural preservation amidst the challenges of globalization.